APAKAH KEPEMILIKAN ASET MEMPENGARUHI JAM KERJA ANAK DI RUMAH TANGGA PERTANIAN? - Wafi, Faiz Abdullah; Apsari, Dhiatira Biananda (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the relationship between household asset ownership in agricultural households and children's working hours. This idea is motivated by previous research which revealed that children from agricultural households are at a higher risk of becoming child laborers, although the number of children involved in labor varies depending on the assets owned by the household. The study employs random effect method as the baseline and tobit panel method as an alternative due to censoring issues on panel data from the Indonesia Family Life Survey (IFLS) for the years 2007 and 2014. The results of the study indicate that the greater the assets owned by agricultural households, the higher the likelihood that children will be spared from engaging in work activities. However, the effect varies depending on the amount of assets held by the household. Through subsample analysis, the reduction in children's working hours has a more significant effect on boys, as they are more likely to work in the agricultural sector, compared to girls, who tend to work more in the domestic sphere. These findings underline the importance of policies that support the welfare of agricultural households, which can reduce children's involvement in labor.